1999
DOI: 10.1104/pp.120.3.787
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Immunolocalization of a Cytosolic Calcium-Binding Protein from Brassica napus and Arabidopsis Pollen1

Abstract: Two low-molecular-weight proteins have been purified from Brassica napus pollen and a gene corresponding to one of them has been isolated. The gene encodes an 8.6-kD protein with two EFhand calcium-binding motifs and is a member of a small gene family in B. napus. The protein is part of a family of pollen allergens recently identified in several evolutionarily distant dicot and monocot plants. Homologs have been detected in Arabidopsis, from which one gene has been cloned in this study, and in snapdragon (Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…The slightly larger hydrodynamic radius of apo Bet v 4 compared to holo Bet v 4 in the NMR translational diffusion and analytical ultracentrifugation measurements (see above) corroborates the results of earlier gel electrophoresis, gel filtration, and size exclusion chromatography experiments on Bet v 4 and other polcalcins. 10,18,26 Depletion of Ca 2þ also causes a reversible reduction of the apparent helicity of Bet v 4 in the CD spectrum (Figure 9), again corroborating the results of earlier studies on Bet v 4 and other polcalcins. 10,12,14,19,29 Like Aln g 4 12 and Phl p 7, 19 the secondary structure of holo Bet v 4 remains stable even at temperatures close to the boiling point of the solvent, whereas apo Bet v 4 is subject to cooperative thermal denaturation at t m ¼ 47 8C (Figure 9).…”
Section: Characterization Of the Structural Transition Upon Ca 21 Depsupporting
confidence: 78%
See 2 more Smart Citations
“…The slightly larger hydrodynamic radius of apo Bet v 4 compared to holo Bet v 4 in the NMR translational diffusion and analytical ultracentrifugation measurements (see above) corroborates the results of earlier gel electrophoresis, gel filtration, and size exclusion chromatography experiments on Bet v 4 and other polcalcins. 10,18,26 Depletion of Ca 2þ also causes a reversible reduction of the apparent helicity of Bet v 4 in the CD spectrum (Figure 9), again corroborating the results of earlier studies on Bet v 4 and other polcalcins. 10,12,14,19,29 Like Aln g 4 12 and Phl p 7, 19 the secondary structure of holo Bet v 4 remains stable even at temperatures close to the boiling point of the solvent, whereas apo Bet v 4 is subject to cooperative thermal denaturation at t m ¼ 47 8C (Figure 9).…”
Section: Characterization Of the Structural Transition Upon Ca 21 Depsupporting
confidence: 78%
“…10,11 A series of allergenic polcalcins have been reported in the literature, namely Aln g 4 from alder (Alnus glutinosa), 12 Ole e 3 from olive (Olea europaea), 13,14 Syr v 3 from lilac (Syringa vulgaris; Ledesma et al, unpublished), Bra n 1 or BPC1 and Bra n 2 from oilseed rape (Brassica napus) as well as Bra r 1 and Bra r 2 from turnip rape (Brassica rapa), 15 -18 Phl p 7 from timothy grass (Phleum pratense), 19 and Cyn d 7 from Bermuda grass (Cynodon dactylon). 20,21 Aln g 4, Syr v 3, Bra n 1 or BPC1, Bra n 2, Bra r 1, Bra r 2 and Phl p 7 as well as the polcalcin APC1 from mouse-ear cress (Arabidopsis thaliana), 18 however, have not been included in the official allergen list of the International Union of Immunological Societies (IUIS) yet and the allergen designations Bra n 1 and Bra r 2 even conflict with two unrelated allergens. 22 These polcalcins share more than 65% sequence identity with Bet v 4 ( Figure 1) and due to their widespread distribution over the plant kingdom and their high IgE cross-reactivity 10 -13,17,19 -21 they might constitute so-called panallergens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunodetection with proteins from germinated pollen indicated that the protein may be utilized in the first half-hour of germination and then is resynthesized. It is known that as the pollen develops it accumulates mRNA required for its rapid germination and tube growth upon landing on the stigma (85). MPCBP may be one of the proteins that is required immediately after hydration especially since it is related to a Ca 2ϩ -mediated pathway that is implicated early in the germination process and tube growth (27).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium, which probably is released by a regulated Ca 2ϩ -ATPase in the papillar cells, is actively taken up by pollen grains (Bednarska, 1993). It may be sensed and sequestered by calcium binding proteins, such as the novel calcium binding protein that is expressed predominantly in the pistil and anthers of Brassica (Furuyama and Dzelzkalns, 1999) or the Brassica napus calcium binding protein 1 (BPC1), which is expressed specifically during pollen maturation (Rozwadowski et al, 1999). BCP1 is of particular interest, because it is localized in the cytosol of mature pollen grains, it leaks into the pollen wall after pollen hydration, and it concentrates near the surface of the elongating pollen tube.…”
Section: Clues From the Physiology And Cell Biology Of Simentioning
confidence: 99%